IMPLEMENTATION OF REWARD SYSTEM TO ENCOURAGE EMPLOYEE PRODUCTIVITY AT ATIQ HOMEKLIK WHOLESALE STORE - M. Ayatullah, Ayat; Cahyawati, Atiq; Iryana Putri, Adela Winda; Sholihat, Urfi; Khaeruman, Khaeruman (Yayasan Education and Social Center, 2024)
This study aims to analyze the effect of reward system implementation on employee productivity at Toko Atiq Homeklik Grosir. This store operates in the retail sector and faces challenges maintaining employee productivity amidst tight competition. The reward system, which includes cash incentives, monthly bonuses, and non-material awards such as recognition of the best employees, is implemented by management to improve employee motivation and performance. The approach used in this study is qualitative, with data collection methods through in-depth interviews, participatory observation, and documentation. The results of the study indicate that although the reward system implemented is effective in several aspects, there is a discrepancy in the application of rewards to individual performance achievements, which impacts the dissatisfaction of some employees. This study concludes that to improve employee productivity, Toko Atiq Homeklik Grosir needs to evaluate and improve the reward system, ensure consistency and fairness in the application of rewards, and align rewards with employee performance goals and achievements. These findings are expected to contribute to the development of HR management, especially in the retail sector, and be a reference for other stores or small businesses that want to increase productivity through an effective reward system.